Pengaruh Pengendalian Emosi Terhadap Orientasi Pelayanan Publik Anggota Polres Sukoharjo - Tiara Fadhilah Hasna Fadholi; Anniez Rachmawati Musslifah (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2024)
This research examines the relationship between the ability to control the emotions of Sukoharjo Police members and their level of public service orientation. Respondents involved members of the Sukoharjo Police with an age range of 18 to 57 years. The type of research is quantitative. Data was collected through a questionnaire that included sample characteristics based on age. Test data requirements include tests of validity, reliability, normality and classical assumptions. The validity test results show a number of valid questions in the variables of emotional control and public service orientation. The reliability test using Cronbach's Alpha confirms that the two variables are reliable. The normality test shows that the data is normally distributed. Classic assumption tests such as linearity and heteroscedasticity tests provide results that support the validity of regression analysis. The simple linear hypothesis test resulted in a significance value (Sig.) of 0.000 and this is smaller than 0.05. So it can be concluded that emotional control has a significant effect on public service orientation. This shows that emotional control has a significant effect on public service orientation.